2013
DOI: 10.1002/mc.22099
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed extract and resveratrol prevent 4‐nitroquinoline 1‐oxide induced oral tumorigenesis in mice by modulating AMPK activation and associated biological responses

Abstract: Preventive measures against oral carcinogenesis are urgently warranted to lower the high morbidity and mortality associated with this malignancy worldwide. Here, we investigated the chemopreventive efficacy of grape seed extract (GSE) and resveratrol (Res) in 4-nitroquinoline-1-oxide (4NQO)-induced tongue tumorigenesis in C57BL/6 mice. Following 8 weeks of 4NQO exposure (100 μg/mL in drinking water), mice were fed with either control AIN-76A diet or diet containing 0.2% GSE (w/w) or 0.25% Res (w/w) for 8 subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 50 publications
0
25
0
1
Order By: Relevance
“…Activation of the AMP‐activated protein kinase (AMPK) signaling pathway, a key regulator of cellular energy metabolism, can play a critical role in the suppression of cell proliferation and induction of apoptosis in various types of malignancies, including OSCC [Kim and He, ; Rehman et al, ; Shrotriya et al, ]. Therefore, we assessed whether the AMPK signaling cascade might contribute to the induction of KB cell apoptosis by sanguinarine.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of the AMP‐activated protein kinase (AMPK) signaling pathway, a key regulator of cellular energy metabolism, can play a critical role in the suppression of cell proliferation and induction of apoptosis in various types of malignancies, including OSCC [Kim and He, ; Rehman et al, ; Shrotriya et al, ]. Therefore, we assessed whether the AMPK signaling cascade might contribute to the induction of KB cell apoptosis by sanguinarine.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, we have mainly focused our attention on recent studies reporting novel targeting HNSCC/OSCC chemoprevention directed at interfering with the commonly deregulated oncogenic EGFR, PI3K, and mTOR pathways either by using selective drugs or common drugs marketed for other chronic conditions (i.e., celecoxib; metformin). Likewise, with the goal of reducing oral carcinogenesis, other novel chemopreventive strategies involving the systemic or topical delivery of natural products like green tea, grape seed extract, freeze-dried raspberries, and strawberries have been also used in high at-risk oral mucosa [77][78][79][80]. An important multidisciplinary area that deserves more attention is associated with the emerging developments in the field of nanochemoprevention.…”
Section: Discussionmentioning
confidence: 99%
“…Through immunohistochemical analyses, the authors show that in tongues from mice given grape seed extract or resveratrol supplementation, there was a decrease in tumor cell proliferation, increase in tumor cell apoptosis, and higher phosphorylated AMPK expression levels. Collectively, these promising findings point to the potential benefit that grape seed extract and resveratrol, possibly via AMPK signaling, might have on the chemoprevention of oral carcinogenesis [77].…”
Section: Natural Compounds As Chemopreventive Agentsmentioning
confidence: 91%
“…A study of human nasopharyngeal carcinoma cells showed that inhibiting autophagy by ATG7-siRNA and bafilomycinA1 increased the apoptotic cell death via increasing the endoplasmic stress and caspase-12 [37]. In an research conducted in a C57BL/6 mice in which tongue tumorigenesis is induced by 4-nitroquinoline-1-oxide (4NQO) revealed that mice fed with grape seed extract or RSV had decreased tumor incidence compared to that of control through regulating AMPK activation thereby inducing apoptosis and autophagy [38]. RSV is found to inhibit cell growth and promote cell differentiation in anaplastic thyroid carcinoma (ATC) cells by activating Notch1 signaling [39].…”
Section: Resveratrol and Head And Neck Cancermentioning
confidence: 99%